2021
DOI: 10.1016/j.micpath.2020.104554
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological similarities between COVID-19 and influenza: Investigating the consequences of Co-infection

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been a global public health emergency since December 2019, and so far, more than 980,000 people (until September 24, 2020) around the world have died. SARS-CoV-2 mimics the influenza virus regarding methods and modes of transmission, clinical features, related immune responses, and seasonal coincidence. Accordingly, co-infection by these viruses is imaginable because some studies have reported several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 161 publications
(163 reference statements)
1
101
0
1
Order By: Relevance
“…To date, at least 13 cases of coinfection of Covid-19 and influenza have been reported in PubMed-listed articles. A larger prevalence of coinfection is suspected, though still under investigation due to the symptoms similarities, as reviewed by H. Khorramdelazad et al (2020) [ 9 ]. In some of the reviewed cases, the coinfection was not more severe than infection with COVID-19 alone [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, at least 13 cases of coinfection of Covid-19 and influenza have been reported in PubMed-listed articles. A larger prevalence of coinfection is suspected, though still under investigation due to the symptoms similarities, as reviewed by H. Khorramdelazad et al (2020) [ 9 ]. In some of the reviewed cases, the coinfection was not more severe than infection with COVID-19 alone [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Co-infection, as well as the risk of reactivation of latent infections, is an important risk in the management of COVID-19 [118] . Studies have shown that baricitinib reactivates viruses, including the varicella zoster, herpes simplex, and Epstein-Barr virus strains.…”
Section: Antiviral Therapy For Covid-19mentioning
confidence: 99%
“…During the outbreak of Ebola virus in 2014 and SARS in 2002, plasma therapy was proposed as an experimental treatment against these viral infections [147] , [148] , [149] . Some evaluations were performed to analyze the clinical effectiveness of convalescent plasma, serum, or hyperimmune immunoglobulin for the treatment of severe viral acute respiratory infections including those due to SARS coronavirus, Spanish influenza A (H1N1), avian influenza A (H5N1), and pandemic influenza A (H1N1) in 2009 [150] . In all cases, hyperimmune immunoglobulin was able to demonstrate a statistically significant reduction in the odds of mortality among those who were treated with convalescent plasma or serum [151] .…”
Section: Immunotherapy Of Covid-19mentioning
confidence: 99%
“…Individuals infected with influenza A and B may have similar symptoms as those infected with SARS-CoV-2 and coinfection of SARS-CoV-2 and influenza [ 31 , 32 ] or other common respiratory pathogens has been reported [ 33 ]. Immunopathological similarities between COVID-19 and influenza has been indicated [ 34 ].…”
Section: Analytical Performance Evaluationmentioning
confidence: 99%